Effects of Globalization on Health Governance in Bangladesh - Rahman, K. M. Atikur (Asian Journal of Social Sciences and Management Studies, 2016)
The paper mainly focuses the adverse impact of globalization on health sector in Bangladesh. Access of the common people to health care has already been difficult due to expensiveness, lack of transparency and good governance in management process, though globalization has expanded the infrastructural and logistic supports of the sectors across the world. In Bangladesh, medicine intake, as if, is a regular having item for the majority of the people – a disease is cured by having one medicine – but another disease is being generated as a result of its side-effects. In addition, medical promotion activities have reached from 500 bed-hospitals to a village medicine vendor that has been made the sector healthy to health business elites. The study mainly aims to explain the adverse influences of globalization on health care system. Besides, specifically it objectifies the corruption and irregularities of medical service focusing the high cost of this facility. The work is an explanatory type of basic study which has been conducted in qualitative approach. Secondary data has been used herein of that sources include the books, journal articles, media report, organizational records, etc. Good governance, proper adjudication activity, commitment of policy makers, skilled human resource management may curb or end the irregularities in Bangladesh health governance.